2008
DOI: 10.1182/blood-2007-10-119073
|View full text |Cite
|
Sign up to set email alerts
|

The combination of granulocyte colony-stimulating factor and stem cell factor significantly increases the number of bone marrow–derived endothelial cells in brains of mice following cerebral ischemia

Abstract: Granulocyte colony-stimulating factor (G-CSF) induces proliferation of bone marrow–derived cells. G-CSF is neuroprotective after experimental brain injury, but the mechanisms involved remain unclear. Stem cell factor (SCF) is a cytokine important for the survival and differentiation of hematopoietic stem cells. Its receptor (c-kit or CD117) is present in some endothelial cells. We aimed to determine whether the combination of G-CSF/SCF induces angiogenesis in the central nervous system by promoting entry of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 31 publications
4
61
0
3
Order By: Relevance
“…Previous studies found that G-CSF-mobilized stem cells infiltrate injured tissues to promote neural repair (28,88,104). As mentioned above, G-CSF displayed capacity to cross the BBB to act upon neurons and glial cells through the G-CSF receptor (134), of which their activation has been demonstrated to downregulate expression of proinflammatory cytokines and to enhance neurogenesis (95,115). The addition of G-CSF to hUCB may promote stemness maintenance and, under appropriate conditions (such as in combination with SCF), guide neural lineage commitment of hUCB (108,116).…”
Section: Combination Therapy Of G-csf and Transplantation Of Umbilicamentioning
confidence: 99%
“…Previous studies found that G-CSF-mobilized stem cells infiltrate injured tissues to promote neural repair (28,88,104). As mentioned above, G-CSF displayed capacity to cross the BBB to act upon neurons and glial cells through the G-CSF receptor (134), of which their activation has been demonstrated to downregulate expression of proinflammatory cytokines and to enhance neurogenesis (95,115). The addition of G-CSF to hUCB may promote stemness maintenance and, under appropriate conditions (such as in combination with SCF), guide neural lineage commitment of hUCB (108,116).…”
Section: Combination Therapy Of G-csf and Transplantation Of Umbilicamentioning
confidence: 99%
“…>7 days post stroke) and global (transient bilateral common carotid artery occlusion) ischaemia. Of note, no functional improvement was seen with G-CSF in the studies of chronic (Zhao et al, 2007a) and global ischaemia; studies co-administering SCF reduced infarct volume in female mice (permanent ischaemia) by 50% (Toth et al, 2008) and improved functional recovery in acute and subacute phases (Kawada et al, 2006).…”
Section: Design Of Studiesmentioning
confidence: 99%
“…13,25 According to our hypothesis, G-CSF co-treatment increased the number of transplanted BMCs within the ischemic brain compared with BMC therapy alone. Because G-CSF is noticeably upregulated as early as 2 hours after ischemia 13 and earlier treatment is usually associated with an improved outcome, we decided to first examine an early treatment initiation with G-CSF.…”
Section: Discussionmentioning
confidence: 99%